Edukasi Upaya Pencegahan Bullying Dengan Media Dongeng Dan Lagu-Lagu Di SDN 02 Bojong Manik - Fadhilah, Nurul (Sinesia : Jurnal Pengabdian Masyarakat, 2024)
This service aims to be a form of educational effort to prevent bullying that is rife at the elementary school education level. The media used in this service are fairy tales and songs to make it interesting and easy to understand by elementary school students.  Indicators of this service's success are students' knowledge that bullying is reprehensible, knowing what behaviors are included in bullying, and knowing what actions can be taken when they get bullied. The phenomenon of bullying that occurs at the elementary school level needs to be followed up seriously. Behavioral coaching is important to do from an early age, character that has been built strong from an early age will be the foundation for a child to behave in the future. Fairy tales and songs are suitable media for elementary school students. The benefit of using fairy tale media is that students will easily understand concretely the cause and effect of a behavior. Song media helps students easily remember new things from a lesson.